Along for the ride [videorecording] - Engesser, Marjorie; Moores, Jim; Simon, Bryan W.; Batinkoff, Randall, 1968-; Haggerty, Dylan; Serna, Pepe, 1944-; Gago, Jenny, 1953-; Freeman, J. E.; Brassard, Denise; Fontaine, Paul (Film editor); Graham, Herb, Jr (MVD Visual, 2022)
"Terry and Vance Cowens, two estranged brothers, meet on a desolate highway in Mexico. Together they drive to a small town where they expect to lay their recently deceased father, Jake, to rest. Stuck in the middle of the desert, the brothers are forced to prop their dead father in the back seat of their car, driving all night as they search for a mortuary. Death, in the form of their father, rides along under the starry night, and compels the two brothers to confront themselves and each other."--Container.